Atypical Hippo signaling network: uncovering novel insights into head and neck cancer biology and advancements in precision intervention - Yang, Pengfei; Li, Shujuan (Frontiers in Cell and Developmental Biology, 2025)
As a major global health challenge with rising incidence and poor prognosis, head and continues to impose a significant clinical burden due to its aggressive biological behavior and frequent therapeutic resistance. Within this context, the atypical Hippo signaling pathway emerges as a crucial regulatory network, integrating diverse components including core kinases (TAO kinases, MAP4K family, NDR1/2 kinases), cell polarity determinants (CRUMBS, SCRIBBLE), junctional adhesion molecules (AMOT family), phosphorylation mediators (14-3-3 proteins), and tumor suppressors (NF2, RASSF family). This multifaceted system governs fundamental cellular processes spanning proliferation, apoptosis, migratory capacity, and immune microenvironment modulation. Notably, post-translational modifications (ubiquitination, acetylation, SUMOylation) of pathway components dynamically regulate the stability and activity of downstream effectors YAP/TAZ, whose sustained activation through molecular aberrations drives tumor progression and treatment resistance in head and neck malignancies.The pathway’s extensive crosstalk with Wnt signaling, NF-κB cascades, and estrogen receptor networks creates context-dependent regulatory plasticity that contributes to tumor heterogeneity. Current therapeutic innovation focuses on molecular diagnostics and precision targeting approaches, including direct YAP/TAZ-TEAD complex inhibitors, upstream receptor modulators, and rational combinations with immune checkpoint blockade. Future investigations should employ multi-omics profiling to delineate tumor subtype-specific regulatory architectures while advancing novel drug delivery platforms. These efforts promise to translate mechanistic insights into multi-targeted therapeutic strategies capable of overcoming resistance mechanisms and improving survival outcomes for this therapeutically challenging malignancy.